Analysis Of The Effectiveness Of Bpjs Health Implementation In Marbau Puskesmas: Balance Between Access And Service Quality - Meiliani, Risa; Syarvina, Wahyu; Fadhila Rahma, Tri Inda (Moneter: Jurnal Keuangan dan Perbankan, 2024)
The aim of this research is to see whether there are still problems in the form of public complaints about the quality of health services which are less than optimal in terms of patient efficacy towards the public services provided. This ineffectiveness can be caused by the unreliability of Puskesmas staff, lack of attention, and lack of empathy in treating patients. Researchers in this study will use qualitative research methods. In general, qualitative methods are used because the existing problems are still unclear, holistic, complex, dynamic and full of meaning, so it is not possible to collect data about social situations using quantitative methods such as tests, questionnaires and interview guides. The findings of this research include: First of all, the issues raised in this research relate to the processes involved in providing BPJS services in accordance with standard operating procedures. Second, the convenience of services offered by health facilities is very good, but the problem is the long queues that have to be waited at the counter and during examinations by doctors. The third consideration is the availability of health services offered by community health centers which are considered health facilities. In terms of human resources, the current availability of health services is still inadequate, however, informants currently state that the services provided to them are quite good. Other factors that contribute to the efficiency of BPJS patient health services are that the services are provided free of charge, the services and treatment are consistent, the inpatient services are complete, and the location is strategic. Meanwhile, the challenges currently faced are a lack of medical personnel, lack of counter service, long queues in examination rooms, as well as a lack of drivers and ambulances for health facilities.